A comparison of constitutional adjudication institutions in Malaysia and Indonesia - Mokhtar, Khairil Azmin; Satriawan, Iwan; Muhammad, Nur Islami (Universiti Putra Malaysia, 2017)
The tyranny of the majority against the rights of the minority is warded off by constitutional safeguards enforced primarily by the court. This is one of the reasons why Malaysia and Indonesia adopt the doctrine of constitutional supremacy when they achieved independence in 1957 and in 1945 respectively. This paper aims at comparing constitutional adjudication as one of the mechanisms of constitutional democracy in both countries. In spite of close proximity in terms of territory and sharing cultural and historical heritages, the two countries have fundamental structural constitutional differences. Malaysia follows the common law model which functions the superior courts as organs of the constitutional adjudications, while Indonesia follows kelsenian model by establishing a separate new court, namely the Constitutional Court.This is a qualitative research that observes the establishment, role and power of constitutional adjudications institutions of both countries. The development and experiences of the institutions in both countries not only shed more lights of constitutional democracy within the two countries but also influenced the process of democratic consolidation in the region.